A expansão das empresas agrárias e seus reflexos jurídicos - Nobre, Bruno Giorgi Ferreira (2016)
The relationship of the earth to the social and economic organization of Brazil is intrinsic. Our origin was due to the exploitation of fruits and subsequently organized the production of foodstuffs meant for export to overseas market. Even when Brazil dissociated itself from the Portuguese Empire, its economy remained tied to colonial productive methods. The evolution of social relationship to the land occurred only from the nineteenth century, with the implementation of productive methodologies and legal changes that resulted in disruption to the production system slaver then current. Since then, in just over a century, the Brazilian government tried to adapt its legal regulations to the existing reality in rural areas, but always under the strong influence of affluent parts of society. Similarly, the urban economic activities expanded, linking to rural activities and demonstrating a hitherto non-existent connection. At the same time, our legal system migrates the economic concept guided the "Trade Act", for the more contemporary concept of "acts of companies." This conjuncture factors, aggregated human action, originates Land Company. Meanwhile, the Agrarian Law is omitted, merely to recognize the Rural Company, diverse legal entity of the Agricultural Company. The distinction is such that there is no consensus among agricultural scholars under the "Rural Enterprise" expression, sometimes treated as synonymous expression of "Agrarian Company", now recognizing it as the sole business activity originally created by the then current rules. In this debate, it is important to highlight the contemporary economic activities carried on by the Company's shareholders, entered the rural countryside and productive environment in a new reality, no longer needing the productive land holdings to identify whether the activity is rural or agrarian. Also stresses that the capital is not at all harmful, responsible for the distribution of wealth and opportunities, albeit incipient. It is therefore the Brazilian state regulation of economic activity and the redefinition of the activities taken as land, so that the latter comply with the constitutional provisions of the Republic of Brasil.